PENGARUH KUALITAS PELAYANAN TERHAI)AP KEPUASAN DAN NIAT BERPERILAKU LOYAL WISATAWAN MANCANEGARA - I Putu Utama (JURNAL KEPARIWISATAAN, 2011)
This research proposes to confirm the effects of service quality on guests satisfaction and behavioral intention loyalty. The data were collected by applying purposive sampling method, which was applied to 200 international tourists staying at a number of five-star hotels in Badung regency. The variables in this study are service quality as an exogenous variable, guests satisfaction as an intervening variable, and behavioral intention as an endogenous variable. The respondents perception is indicated in Likert scale of 5, in which 1 strongly disagrees and 5 strongly agrees with the statements. The data were then analyzed using Structural Equation Modeling (SEM). The questionnaire consisting of 30 questions were tried out for its validity using alpha Pearson Correlation and reliability using Cronbach s alpha. Then, the statistical analysis of Structural Equation Modeling showed that direct effect of service quality to guests' satisfaction was significant ( 7 %), direct effect of guests' satisfaction to behavioral intention loyalty was significant (55.4 %), direct effect of service quality to behavioral intention loyalty was insignificant (19. 1 %), and indirect effect of service quality to behavioral intention loyalty through guests satisfaction was significant ( 48 %).